Analisis Pengaruh Pertumbuhan Ekonomi, IPM, Pengangguran Terbuka dan Angkatan Kerja Terhadap Kemiskinan di Sumatera Utara - Febriangga Sembiring; Tarmizi Tarmizi; Rujiman Rujiman (Jurnal Serambi Engineering, 2020)
Poverty complexity problem is a multidimensional problem, and poverty is related to various aspects of people's lives so that efforts to solve the poverty problem are not easy. This study has purpose to determine and analyze Economic accretion effect, Human development index, Open Unemployment Rate, and Labor Force Participation Rate on Poverty in North Sumatra Province. Secondary data from 2004 - 2017 is used. Data Source is from Board of Central Statistics in North Sumatra Province with testing conducted through the classic judgement exam and statistical exam. With assist of EViews 6.0 statistical data data processing software, data analysis showed that Economic Accretion and idleness Rate variables have a positive and prominent influence on α = 10%, the Human development index variable and the Labor Force Participation Rate are not prominent at α = 10%, on poverty. Regression results are R2 = 0.945055, that shows independent variable used affects dependent variable by 94.51% and the rest 5.49% is affected by other variables beyond analyzed approach.